Religion and Power. An initial discussion - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Sciences, 2010)
The present work is aimed at discussing the relationship between religion and political power. Basically, social psychology like other humanistic sciences had been fully impacted by the effects of second World War. Under such a context, many scholars devoted particular attention to the study of prejudice and discrimination. In the following pages we will try to synthesize how religion contributes for the conformation of ideology and social depictions. In part, this does not suffice to affirm religion is responsible for nationalism but both share analogical element in their respective formations.